FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2011-2013 (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the influence of Capital Structure, Income Growth, Company Size, Liquidity and Earnings Persistence on the Quality of Earnings In Manufacturing Companies Listed on the Stock Exchange. The population of this research is a Manufacturing company listed on the Stock Exchange in 2011 to 2013. The sample in this study as many as 219 companies selected by purposive sampling technique in Manufacturing Companies listed on the Stock Exchange 2011-2013. But after doing outlier sample to 189 companies. Data analysis was performed using multiple linear regression analysis using SPSS 17.00. The results of this study indicate that the Capital Structure, Growth Earnings, Liquidity and Earnings Perisistensis significant positive effect on earnings quality. As for the variable size of the Company has no effect on the Quality of Earning.Keywords: Quality of Earnings, Capital Structure, Income Growth, Company Size, Liquidity, Earnings Persistence